Nursing students' experiences of a pedagogical transition from campus learning to distance learning using digital tools - Ulrica Langegård; Kiana Kiani; Susanne J. Nielsen; Per-Arne Svensson (BMC, 2021)
Abstract Background The use of distance education using digital tools in higher education has increased over the last decade, particularly during the COVID-19 pandemic. Therefore, this study aimed to describe and evaluate nursing students' experiences of the pedagogical transition from traditional campus based learning to distance learning using digital tools. Methods The nursing course Symptom and signs of illness underwent a transition from campus based education to distance learning using digital tools because of the COVID-19 pandemic. This pedagogical transition in teaching was evaluated using both quantitative and qualitative data analysis. Focus group interviews (n = 9) were analysed using qualitative content analysis to explore students' experiences of the pedagogical transition and to construct a web-based questionnaire. The questionnaire comprised 14 items, including two open-ended questions. The questionnaire was delivered to all course participants and responses were obtained from 96 of 132 students (73%). Questionnaire data were analyzed using descriptive statistics and comments from the open-ended questions were used as quotes to highlight the quantitative data. Results The analysis of the focus group interviews extracted three main dimensions: didactic aspects of digital teaching, study environment, and students' own resources. Social interaction was an overall theme included in all three dimensions. Data from the questionnaire showed that a majority of students preferred campus based education and experienced deterioration in all investigated dimensions after the pedagogical transition. However, approximately one-third of the students appeared to prefer distance learning using digital tools. Conclusions The main finding was that the pedagogical transition to distance education reduced the possibility for students' social interactions in their learning process. This negatively affected several aspects of their experience of distance learning using digital tools, such as reduced motivation. However, the heterogeneity in the responses suggested that a blended learning approach may offer pedagogical benefits while maintaining an advantageous level of social interaction.